Virus in the Urine of Healthy People and Patients with Infectious Diseases - Sunho Park; Eui Tae Kim; Jung-Sik Huh (Urogenital Tract Infection)
There has been a sustained effort to overcome the multiple infectious diseases that confront humankind. Urinary tract infections (UTIs) are most commonly caused by bacterial pathogens, primarily Escherichia coli. However, UTIs by viral pathogens have not been significantly reported. The human urinary tract, both in the healthy and diseased states, is home to many viruses despite the traditional belief that urine is sterile in healthy individuals. The most common viral pathogens found in the urinary tract are the human polyomavirus (BK virus), adenovirus, cytomegalovirus, and herpes simplex virus type-1 and type-2. Research should continue to investigate whether these viruses cause clinical infections or are mere colonizers of the urinary tract.